Circulation reactor system for Suzuki-Miyaura coupling reaction with robust palladium-bistheophyllines catalyst in presence of NaCl - Katsuya Kaikake; Kazuki Matsuo; Ren-Hua Jin (Catalysis Communications, 2023)
One of frequent uses of palladium as catalyst is in the Suzuki-Miyaura cross-coupling reaction, which is one of key reactions in the synthesis of pharmaceuticals, fine chemicals, and electronic device materials. In this work, we explored a unique circulation reactor system for Suzuki-Miyaura CC coupling reaction, in which a robust microflower self-assembled from bistheophyllines heptane (PdBTC7) and PdCl2 were packed in column. Injection of the reactants of bromobenzene and phenylboronic acid 51 times in definite interval in the eluent of water/NaCl/ethanol could give continuously biphenyl product, showing the performance of catalyst in 4498 of TON and 8996 h−1 of TOF.